New mechanistic insights into the motile-to-sessile switch in various bacteria with particular emphasis on Bacillus subtilis and Pseudomonas aeruginosa: a review. Issue 4 (21st April 2017) - Sadiq, Faizan A.; Flint, Steve; Li, Yun; Liu, TongJie; Lei, Yuan; Sakandar, Hafiz Arbab; He, GuoQing
Abstract: A biofilm is a complex assemblage of microbial communities adhered to a biotic or an abiotic surface which is embedded within a self-produced matrix of extracellular polymeric substances. Many transcriptional regulators play a role in triggering a motile–sessile switch and in consequently producing the biofilm matrix. This review is aimed at highlighting the role of two nucleotide signaling molecules (c-di-GMP and c-di-AMP), toxin antitoxin modules and a novel transcriptional regulator BolA in biofilm formation in various bacteria. In addition, it highlights the common themes that have appeared in recent research regarding the key regulatory components and signal transduction pathways that help Bacillus subtilis and Pseudomonas aeruginosa to acquire the biofilm mode of life.